Towards Agricultural Modernization and Industrial Development: Examining The Position of Small Holder Farmers in Tanzania - Mrutu, Lukio Lawrence (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
Tanzania is working towards agricultural modernization aiming and improving agricultural productivity. The aim has been to transform traditional agricultural practices with modern practices and help smallholder farmers improve their productivity. However, there has been mixed evidence on the success of such modernization efforts some showing success and others showing the failure. By using available literature, this paper aim at showing the position of smallholder farmers in agricultural modernization process. Findings shows that, agricultural modernization has left smallholder farmers under a marginalized position filled with land grabbing, problems on availability, accessibility, affordability and the quality of agricultural inputs together with the problem of market for agricultural products. As a deliberate effort to improve agriculture sector the government need to increase investment in agricultural inputs by facilitating the availability of industries which produce agricultural inputs like fertilizer. Also, the government should encourage farmers to join into cooperative unions or groups to help them have bargaining power when it comes to marketing their crops.